EFEKTIFITAS METODE ROLE PLAYING UNTUK MENINGKATKAN KOSAKATA ANAK TUNARUNGU - Zulhaida - Filina (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was motivated by the problems faced by Deaf students grade IV / B in SLB Aur West Pasaman River State, the vocabulary of children with hearing impairment is very minimal. And in relation to others we must have sufficient vocabulary for people to communicate smoothly. To overcome these problems is necessary to find a way out, so that children are able to communicate with others. Effectiveness research objective method of role playing to enhance the vocabulary of children with hearing impairment grade IV / B in SLB River State Aur West Pasaman about buying and selling. Type of research is Quasi Experiment, one group pretest-posttest experimental design is implemented in one group without using the comparison group. The subjects were six fourth grade students Deaf / B in SLB Aur West Pasaman River State. Data obtained using the test works. Analysis of the data used is the Mann-Witney U test with test criteria Ha accepted if Uhit> Utab and Ha rejected if Uhit ≤ Utab the significant level of 95% or ɑ = 0.05. The results of data processing show Uhit = 3> Utab = 2, that is accepted and Ho Ha rejected. So, the results showed that the method Playing Effective Role to Increase Vocabulary Deaf Children Class IV / B in SLB Aur West Pasaman River State. For that the school should provide learning about the vocabulary to the child by using role playing so that children can socialize with other people.